Acupuncture in treating cardiovascular disease complicated with depression: A systematic review and meta-analysis - Lu, Lu; He, Weiming; Guan, Dandan; Jiang, Yuanyuan; Hu, Guangyong; Ma, Feixiang; Chen, Li (Frontiers in Psychiatry, 2022)
Background Depression is a serious risk for cardiovascular disease (CVD). Improving depression can alleviate cardiac symptoms and improve quality of life. Studies have shown that acupuncture has a positive effect on depression and CVD. This systematic review and meta-analysis will evaluate the efficacy and safety of acupuncture in the treatment of depression complicated with CVD. Methods We searched PubMed, Embase, Cochrane Library, Web of Science, CNKI, Wanfang, VIP, and China Biomedical Literature databases. Randomized controlled trials of acupuncture vs. standard care or sham acupuncture or antidepressants were included. The retrieval time is from database construction to 07 April 2022. We used the “risk of bias” tool of Cochrane Collaboration, and the Review Manager (RevMan.) Version 5.4.1 for statistics analysis. Primary outcomes included Hamilton scale for depression (HAMD), self-rating depression scale (SDS), and the effective rate of depression. Secondary outcomes included frequency of angina pectoris and visual analogue scale (VAS) scores for angina pain. Results A total of 2,366 studies were screened based on the search strategy. Twelve eligible studies with a total of 1,203 participants have been identified. The result showed that acupuncture reduced the HAMD score [weighted mean difference (WMD): −3.23; 95% confidence interval (CI): −5.38 to −1.09; P = 0.003] and the SDS score (WMD: −1.85; 95% CI: −2.14 to −1.56; P < 0.00001) in patients with depression complicated with CVD. Acupuncture also improved the effective rate of depression (risk ratio: 1.15; 95% CI: 1.03 to 1.29; P = 0.01). The result also showed that acupuncture reduced the attack frequency of angina pectoris (WMD: −4.54; 95% CI: −5.96 to −3.11; P < 0.00001) and the VAS score for angina pain (WMD: −0.72; 95% CI: −1.06 to −0.38; P < 0.0001). This article reviewed the significant advantages of acupuncture for depression and the superiority of acupuncture over no-intervention therapy, antidepressant therapy, and psychotherapy in reducing angina frequency and pain intensity in patients with CVD. Conclusion This systematic review suggested that acupuncture was a good complementary and alternative therapy for CVD complicated with depression. Considering the limitations of the included research literature, it is still necessary to perform multi-center, large-sample, and double-blind high-quality studies to provide higher-level evidence in the later stage. Systematic review registration [https://www.crd.york.ac.uk/prospero/], identifier [CRD42022304957].